Compact Trench Floating Field Rings Termination for 10kV+ Rated SiC n-IGBTs - Lophitis, Neophytos; Gammon, Peter M.; Renz, A. Benjamin; Dai, Tianxiang; Tiwari, Amit K.; Trajkovic, Tatjana; Mawby, Philip A.; Udrea, Florin; Antoniou, Marina (My University, 2022)
This work presents the design methodology and performance of a compact edge termination structure aiming 10kV+ rated Silicon Carbide (SiC) devices. Standard Floating Field Rings (FFRs) for such high voltage rating SiC devices are not favored because they are inefficient in terms of the achievable breakdown voltage as a percentage of the 1D maximum, consume large chip area, require high implantation energies and small gaps between rings which can violate fabrication limits. We show that the implantation of Aluminium at the bottom of carefully positioned trenches can be analogous to deep Aluminium implantation in terms of performance, thus annulling the need for small gaps between rings and MeV ion implantation. We optimize the distribution of trenches by placing them in multiple zones of different expansion coefficient. The proposed multi expansion ratio Trench FFR termination was utilized to terminate the active area of a 10kV rated Punch Through n-IGBT having 0.8 μm p-body and 100 μm, 3×1014 cm-3 drift region. We found the 0.6 – 0.8 µm to be the most optimum trench depth, achieving over 10 kV within less than 500 μm of termination length.
Keywords: Edge Termination; Floating Field Rings; IGBT; Silicon Carbide; Trench